Beyond Interdisciplinary: Igniting Transdisciplinary Thinking in Tomorrow’s Music Technology Graduates - Mark De Zwaan (Journal of the Association for Technology in Music Instruction, 2025)
Outwardly, this presentation is an inquest into the structural quandaries of curricular design in music technology—a practical extension to the seminal discussion about music technology curriculum launched by Carola Boehm (2007). I recently pioneered a new BSc degree program in Digital Music Technology at my institution, obtaining the support of four departments across campus to manifest an interdisciplinary implementation, yet the curricular structure governing our degree programs was generally incompatible with Boehm’s foremost recommendations. This led me down the very curricular path she rejected as “modernist”: derived from 18th-century concepts of the university in which interdisciplinarity was realized through the acute study of each constituent, “pure” field. According to Boehm, too much is hefted upon the shoulders of the learner under this model—the pupil is often left alone with the task of actualizing interdisciplinary understanding between the different domains. Boehm instead advocates a move toward “post-modernist” curricula, which favor nuanced courses that expressly highlight interdisciplinarity. From this pronouncement I developed a temporary conviction that I had inadvertently piloted my curriculum in the wrong direction. At its core, this presentation motivates a philosophical edict for music technology and its pedagogy, deduced from my crusade to transcend the perceived shortcomings of my unavoidably modernist curricular structure. A study mapping the "employability" of Australian music-technology graduates according to curricular attributes of the nation’s degree programs posed the idea of music technology as transdisciplinary (Klein & Lewandowski-Cox, 2019). In this I detected a novel perspective about the field’s multidisciplinary makeup that not only maintains compatibility with established interdisciplinary aspirations but also encourages curricular designers to regard core coursework in music technology as an optimal vehicle for pushing students toward fresh thinking through collective assimilation of individual disciplinary perspectives. References: Boehm, C. (2007). The discipline that never was: current developments in music technology in higher education in Britain. Journal of Music, Technology and Education 1(1), 7–21. https://doi.org/10.1386/jmte.1.1.7/1 Klein, E., and Lewandowski-Cox, J. (2019). Music technology and Future Work Skills 2020: An employability mapping of Australian undergraduate music technology curriculum. International Journal of Music Education, 37(4), 636-653. https://doi.org/10.1177/0255761419861442